Guinea : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Despite notable potential in mining and agriculture, Guinea's macroeconomic situation deteriorated between 2002 and 2006. Since April 2007, the government has begun to stabilize the economy by tightening fiscal and monetary policies. Achieving the targeted completion rate in the education sector will require considerable financial and human resources. IMF staff recognize the significant potential of agriculture in setting the stage for accelerated and more inclusive economic growth in Guinea. The macroeconomic objectives in the Poverty Reduction Strategy Paper (PRSP-II) are broadly consistent with the most recent medium-term macroeconomic framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet